Double-shell coated hydrated salt phase change microcapsule and preparation method thereof

Through the double-shell coating technology of modified boron nitride and inorganic hydrated salt, the problem of reduced heat storage capacity of hydrated salt phase change microcapsules after multiple cycles has been solved, and phase change microcapsules with high thermal conductivity and cycle stability have been achieved. capsule.

CN119351059AActive Publication Date: 2025-01-24DONGGUAN UNIV OF TECH

Patent Information

Application Number
CN202411422864.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-24
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The existing hydrated salt phase-change microcapsules have reduced heat storage capacity after multiple cycles, and the thermal conductivity of the inorganic shell material is low, which limits its thermal diffusion rate.

Method used

Use modified boron nitride to mix with inorganic hydrophilic salt, and disperse ultrasonic, as component A; mix the modified boron nitride with cycloinnane, disperse ultrasonic, as component B; add component A to component B, and Add the surfactant, the silicane coupling agent, the ahead of the silicon dioxide, and the ammonia water, and the stirring reaction to form a phase -changing micro -capsule with a double -shell cover.

Benefits of technology

It improves the coating rate and phase change heat storage density of hydrated salt, combines latent heat storage in the low-temperature section and thermal decomposition heat storage in the high-temperature section, and improves thermal conductivity and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351059A_ABST
    Figure CN119351059A_ABST
Patent Text Reader

Abstract

The invention relates to the field of phase change microcapsules, and particularly discloses a double-shell coated hydrated salt phase change microcapsule and a preparation method thereof. Comprising the following steps: mixing modified boron nitride with inorganic hydrated salt, heating in a water bath until the temperature is 5-20 DEG C higher than the melting point of an inorganic hydrated salt phase change material, and ultrasonically dispersing to obtain a component A; mixing the modified boron nitride with cyclohexane, and performing ultrasonic dispersion to obtain a component B; adding the component A into the component B, sequentially adding a surfactant, a silane coupling agent, a silicon dioxide precursor and ammonia water under the conditions of constant-temperature water bath and stirring, and stirring and reacting for 8-24 hours to obtain a component C; and washing, filtering and drying the component C to obtain the double-shell coated hydrated salt phase change microcapsule.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of phase-change microcapsules, in particular to a double-shell coated hydrated salt phase-change microcapsule and a preparation method thereof. Background Art

[0002] Inorganic hydrated salts are a key type of energy material; they play a key role in many important fields such as power battery temperature control, solar thermal energy conversion, building energy storage and home heating; however, hydrated inorganic salts have problems such as large supercooling, easy phase separation, thermal instability, low thermal conductivity, etc., which limit their application in practice. Studies have found that if hydrated salts are encapsulated as core materials in inorganic or organic shell materials, the preparation of phase change microcapsules with a core-shell structure can effectively solve the above-mentioned problems of hydrated salts. In the prior art, the shell materials of hydrated salt phase change microcapsules are generally composed of organic materials or inorganic materials; compared with organic shell materials, inorganic shell materials have the advantages of high mechanical strength, good chemical stability, high thermal conductivity, non-flammability, low cost and environmental optimization, and have attracted widespread attention from researchers.

[0003] However, the reported preparation process of phase-change microcapsules with hydrated salts coated with inorganic shell materials generally starts with coating a saturated solution of hydrated salts. Only when the excess free water evaporates can the crystalline hydrated salts be precipitated. Moreover, a small amount of crystalline water is still converted into free water during the hot and cold cycle of the hydrated salts, resulting in a decrease in the heat storage capacity of the phase-change microcapsules after multiple cycles. In addition, the inorganic shell material is mainly silica with a low thermal conductivity, which limits its thermal diffusion rate.

[0004] Chinese patent CN102676124B discloses an inorganic hydrated salt phase change energy storage microcapsule and a preparation method thereof. The microcapsule uses a saturated salt solution formed by an inorganic hydrated salt and 20% to 30% deionized water by relative mass as the core material, and a polymer as the shell material. Then, by selecting a suitable organic solvent and supplementing it with a surfactant, the core material and the shell material are made to form a uniformly dispersed mixed solution under the action of ultrasound. By adding functional additives such as initiators, lubricants, stabilizers and polymerization inhibitors, the polymer monomer is suspended, polymerized and solidified in the mixed solution under reaction conditions, and then coated with the core material to form a phase change microcapsule. This invention patent effectively solves the problems of supercooling and phase separation of hydrated salt phase change materials. However, the phase change microcapsules prepared by using a polymer material with flammability and low thermal conductivity as the shell material are still flammable and have a low thermal conductivity. Deionized water is added during the preparation process, and the core material may contain excess water in addition to the inorganic hydrated salt.

[0005] Chinese patent CN104874337B discloses a method for preparing silica-coated crystalline hydrated salt phase change material microcapsules. This invention patent adopts an in-situ polymerization method and uses silica as a shell material to achieve the encapsulation of crystalline hydrated salt phase change materials, solving the problems of supercooling of crystalline hydrated salts, phase separation, and leakage during the phase change process of phase change materials. The resulting phase change microcapsules have a large latent heat of phase change. However, this invention patent uses silica with a low thermal conductivity as a shell material, which limits the thermal conductivity of the phase change microcapsules; the preparation process mixes the hydrated salt with a large amount of water to obtain a saturated crystalline hydrated salt solution, so the core material of the prepared phase change microcapsules may contain excess water in addition to the inorganic hydrated salt; this invention patent does not involve research on the thermal decomposition temperature and thermal decomposition enthalpy of the phase change microcapsules; in addition, this invention patent does not involve the cyclic stability of the phase change microcapsules.

[0006] Chinese patent CN114316916A discloses a double-layer nano-oxide-coated inorganic hydrated salt phase change material and its preparation method. This patent utilizes inorganic nanoparticles as an emulsifier, a hydrated salt material as the aqueous phase, and an organic solvent as the oil phase, reacting with a sol-gel reaction precursor and catalyst to produce a phase change material. This phase change material solves the problem of failure caused by contact between free water and the hydrated salt phase change material during the sol-gel reaction due to the presence of inorganic nanoparticles at the oil-water interface in the reverse Pickering emulsion. Furthermore, the phase change material prepared by coating the hydrated salt with a double layer of inorganic nano-oxide improves the material's mechanical strength and thermal conductivity. While the patent discloses a double-layer shell structure, it does not address research into the thermal decomposition temperature, thermal decomposition enthalpy, or cyclic stability of the phase change microcapsules.

[0007] Hexagonal boron nitride (h-BN) is a high-performance material renowned for its high thermal stability, excellent electrical insulation, good thermal conductivity, chemical inertness, low density, and lubricity. It is widely used in high-temperature applications, electronics, optics, chemistry, and mechanical engineering. Furthermore, modified boron nitride nanosheets can self-assemble at the oil-water interface to form stable oil-in-water (O / W) and water-in-oil (W / O) Pickering emulsions. However, there are currently no reports of salt-hydrate phase-change microcapsules encapsulated with a double-layer inorganic hybrid shell using a salt-hydrate / polar solvent template stabilized by modified boron nitride nanosheets. Using modified boron nitride, which exhibits high thermal conductivity, good thermal stability, and emulsifying properties, as a stabilizer for the salt-hydrate emulsion and a shell material for the phase-change microcapsules, could potentially allow the preparation of salt-hydrate phase-change microcapsules with high thermal conductivity and excellent cyclic stability without the introduction of free water.

[0008] Therefore, we propose a double-shell coated hydrated salt phase change microcapsule and a preparation method thereof. Summary of the Invention

[0009] The object of the present invention is to provide a double-shell coated hydrated salt phase change microcapsule and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0010] A method for preparing double-shell coated hydrated salt phase change microcapsules comprises the following steps:

[0011] S1: (1) mixing modified boron nitride and inorganic hydrated salt, and ultrasonically dispersing them to obtain component A;

[0012] (2) mixing the modified boron nitride with cyclohexane and dispersing by ultrasonication to obtain component B;

[0013] (3) adding component A to component B, and sequentially adding a surfactant, a silane coupling agent, a silica precursor, and aqueous ammonia in a constant temperature water bath under stirring conditions, and stirring and reacting for 8 to 24 hours to obtain component C; wherein component C is a phase change microcapsule suspension;

[0014] S2: Component C is washed, filtered, and dried to obtain double-shelled hydrated salt phase change microcapsules.

[0015] More optimally, the raw materials of component C include the following components: in mass percentage, 5-20wt% inorganic hydrated salt, 0.1-1wt% modified boron nitride, 0.2-1wt% surfactant, 1-3wt% silane coupling agent, 5-15wt% silica precursor, 10-30% ammonia water, and the balance is cyclohexane.

[0016] More optimally, the modified boron nitride is hydroxylated boron nitride nanosheets with a diameter of 50 to 500 nm and an average diameter of <150 nm.

[0017] More preferably, the inorganic hydrated salt includes one or more of sodium thiosulfate pentahydrate, sodium acetate trihydrate, disodium hydrogen phosphate dodecahydrate, sodium sulfate decahydrate, and calcium chloride hexahydrate.

[0018] More preferably, the surfactant includes but is not limited to one or more of cetyltrimethylammonium bromide, sodium lauryl sulfate, Triton X-100, Tween 80 and Span 80.

[0019] More optimally, in S1, the silane coupling agent includes one or both of 3-aminopropyltriethoxysilane and γ-aminopropyltriethoxysilane.

[0020] More optimally, the silicon dioxide precursor is tetraethyl silicate.

[0021] The more optimized S1 (1) and (2) have the same ultrasonic dispersion process, which are: the temperature is 5 to 20°C higher than the melting point of the inorganic hydrated salt; the ultrasonic power is 400 to 700 W, and the ultrasonic time is 10 to 15 minutes.

[0022] More optimally, the water bath temperature is 5-20° C. higher than the melting point of the inorganic hydrated salt, the stirring speed is 400-600 rpm, and the time interval for adding each raw material in sequence is 1-15 minutes.

[0023] Compared with the prior art, the present invention has the following beneficial effects: the present invention mixes modified boron nitride with an inorganic hydrated salt and ultrasonically disperses the mixture to obtain component A; the modified boron nitride is mixed with cyclohexane and ultrasonically dispersed to obtain component B; component A is added to component B, and a surfactant, a silane coupling agent, a silica precursor and ammonia water are sequentially added in a constant temperature water bath under stirring conditions, and the mixture is stirred and reacted for 8 to 24 hours to obtain component C; and component C is washed, filtered and dried to obtain double-shell coated hydrated salt phase change microcapsules.

[0024] (1) The double-shelled hydrated salt phase change microcapsules prepared by the present invention have a high hydrated salt coverage rate and a large phase change heat storage density.

[0025] (2) The double-shelled hydrated salt phase change microcapsules prepared by the present invention have both the properties of latent heat storage in the low-temperature range (<100°C) and thermal decomposition heat storage in the high-temperature range (>100°C). The latent heat storage in the low-temperature range is derived from the phase change of the hydrated salt, with a phase change enthalpy of 71.9 to 148.1 J / g, while the latent heat storage in the high-temperature range is derived from the thermal decomposition of the hydrated salt, with a thermal decomposition enthalpy of 306.6 to 542.8 J / g, which can meet the high heat storage density requirements in different temperature ranges.

[0026] (3) The double-shell coated hydrated salt phase change microcapsules prepared by the present invention use silicon dioxide and modified boron nitride nanomaterials with high thermal conductivity as double-layer shell materials, which solves the problems of core material leakage and volatilization of free water generated after the hydrated salt phase change material melts in the low temperature range, thereby improving the stability of the hydrated salt and the thermal conductivity of the phase change microcapsules.

[0027] (4) The double-shelled hydrated salt phase change microcapsules prepared by the present invention have good cyclic stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0029] Figure 1 This is an SEM image of the double-shelled hydrated salt phase change microcapsules prepared in Example 1 of the present invention;

[0030] Figure 2 DSC comparison chart of double-shelled hydrated salt phase change microcapsules prepared in Examples 1, 5 and 6 of the present invention;

[0031] Figure 3 The DSC graphs of the double-shelled hydrated salt phase change microcapsules prepared in Example 1 of the present invention before and after thermal cycling;

[0032] Figure 4 This is the DSC graph of the silica-coated hydrated salt phase change microcapsules prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The following will clearly and completely describe the technical solutions in the examples of implementation of the present invention in conjunction with the accompanying drawings. Obviously, the examples of implementation described are only part of the examples of implementation of the present invention, not all of the examples of implementation. Based on the examples of implementation of the present invention, all other examples of implementation obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.

[0034] The following description sets forth many specific details to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the scope of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below. The raw material for the modified boron nitride in this embodiment is hexagonal boron nitride powder, provided by Shanghai Aladdin Reagent Co., Ltd., obtained by ball milling-assisted exfoliation. The specific preparation method is referenced in Chinese Patent CN116814223A.

[0035] According to Chinese patent CN116814223A: Boron nitride nanosheets and sucrose (provided by Shanghai Aladdin Reagent Co., Ltd.) are weighed in a mass ratio of 1:5; the boron nitride nanosheets and sucrose are first mixed, then ball-milled for 12 to 14 hours, and washed with a large amount of deionized water; ultrasonically dispersed for 20 minutes, centrifuged, and freeze-dried to obtain hydroxylated modified boron nitride.

[0036] Sodium thiosulfate pentahydrate, sodium sulfate decahydrate, sodium dodecyl sulfate (SDS), and Triton X-100 were provided by Shanghai Aladdin Reagent Co., Ltd.; cetyltrimethylammonium bromide (CTAB) was provided by Tianjin Damao Chemical Reagent Factory; 3-aminopropyltriethoxysilane (APTs) was provided by Shanghai MacLean Biochemical Co., Ltd.; tetraethyl silicate (TEOs) was provided by Shanghai MacLean Biochemical Co., Ltd.; 25% ammonia water was provided by Shanghai Aladdin Reagent Co., Ltd.; and anhydrous ethanol was provided by Tianjin Best Chemical Co., Ltd.

[0037] Example 1: A method for preparing double-shelled hydrated salt phase change microcapsules, comprising the following steps:

[0038] 0.014 g of modified boron nitride was mixed with 1.99 g of sodium thiosulfate pentahydrate, heated in a water bath to 60°C, and after the sodium thiosulfate pentahydrate was melted, ultrasonic dispersion was performed in a cell crusher at an ultrasonic power of 600 W for 10 minutes to obtain component A; 0.125 g of modified boron nitride was mixed with 12.5 g of cyclohexane, heated in a water bath to 60°C, and ultrasonic dispersion was performed in a cell crusher at an ultrasonic power of 600 W for 10 minutes to obtain component B; component A was added to component B, and under the conditions of a constant temperature water bath temperature of 60°C and a magnetic stirring speed of 500 rpm, 0.1 g of CTAB and 0.3 mL of APTs were added in sequence, with an interval of 10 minutes between the addition of the two raw materials, followed by the addition of 2 mL of TEOs, and continued stirring for 1 minute before adding 4.5 mL 25% ammonia water was stirred at 500 rpm for 16 hours to obtain component C. Component C was then filtered through an organic filter membrane, washed three times with anhydrous ethanol, and dried at room temperature for 48 hours to obtain double-shelled hydrated salt phase-change microcapsules. The phase change enthalpy and decomposition enthalpy of the double-shelled hydrated salt phase-change microcapsules were 125.6 J / g and 522.2 J / g, respectively. After multiple thermal cycles, the phase change enthalpy and decomposition enthalpy of the phase-change microcapsules remained at 117.1 J / g and 498.6 J / g, respectively, demonstrating good cyclic stability.

[0039] Example 2: A method for preparing double-shelled hydrated salt phase-change microcapsules, comprising the following steps:

[0040] 0.014 g of modified boron nitride was mixed with 1.9 g of sodium thiosulfate pentahydrate, heated in a water bath to 60°C, and after the sodium thiosulfate pentahydrate was melted, ultrasonic dispersion was performed in a cell crusher at an ultrasonic power of 600 W for 10 minutes to obtain component A; 0.125 g of modified boron nitride was mixed with 12.5 g of cyclohexane, heated in a water bath to 60°C, and ultrasonic dispersion was performed in a cell crusher at an ultrasonic power of 600 W for 1 minute to obtain component B; component A was added to component B, and 0.1 g of CTAB was added under the conditions of a constant temperature water bath temperature of 60°C and a magnetic stirring speed of 500 rpm. Stirring was continued for 15 minutes, 0.3 mL of FD-550 was added, and then 2 mL of TEOs was quickly added. After stirring for 10 minutes, 3 mL of 25% ammonia water, continue heating and stirring in a water bath at 60°C and 500 rpm, and react for 16 hours to obtain component C; pour component C onto an organic filter membrane for filtration, then wash three times with anhydrous ethanol, and dry at room temperature for 48 hours to obtain double-shelled hydrated salt phase change microcapsules; the phase change enthalpy and decomposition enthalpy of the double-shelled hydrated salt phase change microcapsules are 112 J / g and 449.8 J / g, respectively.

[0041] Example 3: A method for preparing double-shelled hydrated salt phase-change microcapsules, comprising the following steps:

[0042] 0.02 g of modified boron nitride was mixed with 2.48 g of sodium sulfate decahydrate, heated in a water bath to 45°C, and after the sodium sulfate decahydrate melted, ultrasonic dispersion was performed in a cell crusher at an ultrasonic power of 500 W for 15 minutes to obtain component A; 0.125 g of modified boron nitride was mixed with 12.5 g of cyclohexane, heated in a water bath to 45°C, and ultrasonic dispersion was performed in a cell crusher at an ultrasonic power of 600 W for 12 minutes to obtain component B; component A was added to component B, and 0.1 g of CTAB was added under a constant temperature water bath temperature of 45°C and a magnetic stirring speed of 500 rpm. Stirring was continued for 15 minutes, 0.4 mL of APTs was added, and then 2 mL of TEOs was quickly added. After stirring for 12 minutes, 4.5 mL of 25% ammonia water, continue heating and stirring in a water bath at a temperature of 45°C and a rotation speed of 500 rpm, and react for 16 hours to obtain component C; pour component C onto an organic filter membrane for filtration, then wash three times with anhydrous ethanol, and dry at room temperature for 72 hours to obtain double-shell coated hydrated salt phase change microcapsules; the phase change enthalpy and decomposition enthalpy of the double-shell coated hydrated salt phase change microcapsules are 101.1 J / g and 364.5 J / g, respectively.

[0043] Example 4: A method for preparing double-shelled hydrated salt phase-change microcapsules, comprising the following steps:

[0044] 0.011 g of modified boron nitride was mixed with 1.49 g of sodium thiosulfate pentahydrate, heated in a water bath to 60°C, and after the sodium thiosulfate pentahydrate was melted, ultrasonic dispersion was performed by a cell crusher at an ultrasonic power of 650 W for 8 minutes to obtain component A; 0.125 g of modified boron nitride was mixed with 12.5 g of cyclohexane, heated in a water bath to 60°C, and ultrasonic dispersion was performed by a cell crusher at an ultrasonic power of 550 W for 11 minutes to obtain component B; component A was added to component B, and 0.1 g of SDS was added under a constant temperature water bath temperature of 60°C and a magnetic stirring speed of 500 rpm. Stirring was continued for 15 minutes, 0.2 mL of APTs was added, and then 2 mL of TEOs was quickly added. After stirring for 10 minutes, 3 mL of 25% ammonia water, continue heating and stirring in a water bath at 60°C and 500 rpm, and react for 16 hours to obtain component C; pour component C onto an organic filter membrane for filtration, then wash three times with anhydrous ethanol, and dry at room temperature for 48 hours to obtain double-shelled hydrated salt phase change microcapsules; the phase change enthalpy and decomposition enthalpy of the double-shelled hydrated salt phase change microcapsules are 88.4 J / g and 366.7 J / g, respectively.

[0045] Implementation Case 5: A method for preparing double-shelled hydrated salt phase-change microcapsules, comprising the following steps:

[0046] 0.022 g of modified boron nitride was mixed with 2.98 g of sodium thiosulfate pentahydrate, heated in a water bath to 60°C, and after the sodium thiosulfate pentahydrate was melted, ultrasonic dispersion was performed in a cell crusher at an ultrasonic power of 600 W for 10 minutes to obtain component A; 0.125 g of modified boron nitride was mixed with 12.5 g of cyclohexane, heated in a water bath to 60°C, and ultrasonic dispersion was performed in a cell crusher at an ultrasonic power of 600 W for 10 minutes to obtain component B; component A was added to component B, and 0.1 g of CTAB was added under the conditions of a constant temperature water bath temperature of 60°C and a magnetic stirring speed of 500 rpm. Stirring was continued for 15 minutes, 0.5 mL of APTs was added, and then 3 mL of TEOs was quickly added. After stirring for 12 minutes, 6 mL 25% ammonia water, continue heating and stirring in a water bath at 60°C and 500 rpm, and react for 16 hours to obtain component C; pour component C onto an organic filter membrane for filtration, then wash three times with anhydrous ethanol, and dry at room temperature for 72 hours to obtain double-shell coated hydrated salt phase change microcapsules; the phase change enthalpy and decomposition enthalpy of the double-shell coated hydrated salt phase change microcapsules are 148.1 J / g and 603.1 J / g, respectively.

[0047] Example 6: A method for preparing double-shelled hydrated salt phase-change microcapsules, comprising the following steps:

[0048] 0.011 g of modified boron nitride was mixed with 1.49 g of sodium thiosulfate pentahydrate, heated in a water bath to 60°C, and after the sodium thiosulfate pentahydrate was melted, ultrasonic dispersion was performed in a cell crusher at an ultrasonic power of 600 W for 10 minutes to obtain component A; 0.125 g of modified boron nitride was mixed with 12.5 g of cyclohexane, heated in a water bath to 60°C, and ultrasonic dispersion was performed in a cell crusher at an ultrasonic power of 600 W for 10 minutes to obtain component B; component A was added to component B, and 0.1 g of Triton X-100 was added under a constant temperature water bath temperature of 60°C and a magnetic stirring speed of 500 rpm. Stirring was continued for 12 minutes, 0.1 mL of APTs was added, and then 2 mL of TEOs was quickly added. After stirring for 12 minutes, 3 mL of 25% ammonia water, continue heating and stirring in a water bath at 60°C and 500 rpm, and react for 16 hours to obtain component C; pour component C onto an organic filter membrane for filtration, then wash three times with anhydrous ethanol, and dry at room temperature for 72 hours to obtain double-shell coated hydrated salt phase change microcapsules; the phase change enthalpy and decomposition enthalpy of the double-shell coated hydrated salt phase change microcapsules are 71.9 J / g and 306.6 J / g, respectively.

[0049] Comparative case 1 is silica-coated hydrated salt phase change microcapsules;

[0050] 2 g of sodium thiosulfate pentahydrate was heated in a water bath to 60°C until completely dissolved, obtaining component A. 12.5 g of cyclohexane was heated in a water bath to 60°C to obtain component B. Component A was added to component B, and 0.1 g of CTAB and 0.3 mL of APTs were added sequentially at a 10-minute interval in a constant-temperature water bath at 60°C and a magnetic stirrer at 500 rpm. Subsequently, 2 mL of TEOs was rapidly added, and stirring was continued for 10 minutes. Then, 4.5 mL of 25% aqueous ammonia was added, and heating and stirring in a water bath at 60°C and 500 rpm were continued for 16 hours to obtain component C. Component C was filtered through an organic filter membrane, washed three times with anhydrous ethanol, and dried at room temperature for 48 hours to obtain double-shelled hydrated salt phase change microcapsules. The DSC graph of the double-shelled hydrated salt phase change microcapsules showed only one thermal decomposition peak, with almost no phase change enthalpy, and a decomposition enthalpy of 208.6 J / g.

[0051] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.

[0052] Finally, it should be noted that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art will be able to modify the technical solutions described in the aforementioned embodiments or substitute equivalents for some of the technical features. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention shall be included within the scope of protection of the present invention.

Claims

1. A method for preparing double-shell coated hydrated salt phase change microcapsules, characterized in that: The following steps are involved: S1: (1) mixing the modified boron nitride and the inorganic hydrated salt, and dispersing them by ultrasonication to obtain component A; (2) mixing the modified boron nitride with cyclohexane and dispersing by ultrasonication to obtain component B; (3) adding component A to component B, and adding a surfactant, a silane coupling agent, a silica precursor and aqueous ammonia in sequence in a constant temperature water bath under stirring conditions, and stirring the reaction for 8 to 24 hours to obtain component C; S2: Component C is washed, filtered and dried to obtain double-shell coated hydrated salt phase change microcapsules.

2. The method for preparing a double-shell coated hydrated salt phase change microcapsule according to claim 1, characterized in that: The raw materials of component C include the following components: in mass percentage, 5-20wt% inorganic hydrated salt, 0.1-1wt% modified boron nitride, 0.2-1wt% surfactant, 1-3wt% silane coupling agent, 5-15wt% silicon dioxide precursor, 10-30% ammonia water, and the balance is cyclohexane.

3. The method for preparing a double-shell coated hydrated salt phase change microcapsule according to claim 1, characterized in that: The modified boron nitride is a hydroxylated boron nitride nanosheet with a diameter of 50 to 500 nm and an average diameter of less than 150 nm.

4. The method for preparing a double-shell coated hydrated salt phase change microcapsule according to claim 1, characterized in that: The inorganic hydrated salt includes one or more of sodium thiosulfate pentahydrate, sodium acetate trihydrate, disodium hydrogen phosphate dodecahydrate, sodium sulfate decahydrate, and calcium chloride hexahydrate.

5. The method for preparing a double-shell coated hydrated salt phase change microcapsule according to claim 1, characterized in that: The surfactant includes one or more of cetyltrimethylammonium bromide, sodium lauryl sulfate, Triton X-100, Tween 80 and Span 80.

6. The method for preparing a double-shell coated hydrated salt phase change microcapsule according to claim 1, characterized in that: In S1, the silane coupling agent includes one or both of 3-aminopropyltriethoxysilane and γ-aminopropyltriethoxysilane.

7. The method for preparing a double-shell coated hydrated salt phase change microcapsule according to claim 1, characterized in that: The silicon dioxide precursor is tetraethyl silicate.

8. The method for preparing a double-shell coated hydrated salt phase change microcapsule according to claim 1, characterized in that: In (1) and (2) of S1, the ultrasonic dispersion process is the same, that is, the temperature is 5 to 20° C. higher than the melting point of the inorganic hydrated salt; the ultrasonic power is 400 to 700 W; and the ultrasonic time is 10 to 15 minutes.

9. The method for preparing a double-shell coated hydrated salt phase change microcapsule according to claim 1, characterized in that: The water bath temperature is 5-20° C. higher than the melting point of the inorganic hydrated salt, the stirring speed is 400-600 rpm, and the time interval between each raw material when adding them sequentially is 1-15 minutes. 10 . Double-shell coated hydrated salt phase change microcapsules prepared according to the method for preparing double-shell coated hydrated salt phase change microcapsules according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Inorganic hydrous salt phase change energy storage microcapsule and preparation method thereof

    CN102676124B

  • A preparation method of silicon dioxide-coated crystalline hydrated salt phase-change material microcapsules

    CN104874337B

  • Double-layer nano oxide coated inorganic hydrated salt phase change material and preparation method thereof

    CN114316916A

  • Nano thermal conductivity enhanced microcapsule composite phase change material and preparation method thereof

    CN106085368A

  • Inorganic hydrated salt phase change energy storage microcapsule and preparation method thereof

    CN106244117A

Cited By

  • Preparation method and application of hydrated salt phase change microcapsule modified diaphragm

    CN121097342A